Behavior Change Theories: a New Medical Education Paradigm? - Rios,Leonardo Essado (2020)
Abstract: A critical perspective on the importance of evidence-based behavior change theories for medical education is presented. Numerous theoretical models have been proposed to explain behavior changes, with two theories currently emerging as a new paradigm, namely the Behaviour Change Wheel (BCW) and the Prime Theory of Motivation. Behind this is the fact that these theories were proposed based on comprehensive literature review about explanatory models of behavioral changes, in addition to consensus among experts. The basic principle is that any change in behavior necessarily involves three interrelated aspects: capability, opportunity, and motivation. In the present essay, these theories were addressed with a view to problems involving behaviors in medical education, and emphasis on the problem of obsolete teaching practices in the training of health professionals. Assuming that good teachers have a global view of the teaching profession, and not merely of their specialty, interventions to change outdated teaching performances among health educators should start by understanding their motivation to change. It is also necessary to investigate their knowledge and skills about innovative teaching-learning methods (capability), as well as whether the environment supports methodological diversification and innovation (opportunity). In summary, evidence-based behavior change theories may represent a new paradigm for medical education when the goal involves overcoming behavioral problems.